2020
DOI: 10.1021/acssuschemeng.9b05755
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Various Deep Eutectic Solvents on the Sustainable Synthesis of MgFe2O4 Nanoparticles for Simultaneous Electrochemical Determination of Nitrofurantoin and 4-Nitrophenol

Abstract: The innovations in the field of green chemistry have expedited the pace of advances in varied research areas ranging from the development of diverse routes for the material synthesis to designer solvents. Deep eutectic solvents (DESs) integrating the metrics and principles of sustainability substitute the traditional hazardous and volatile reagents, which is significantly attracting the attention of research and industrial sectors. In view of that, we introduce deep eutectic-mediated solid-state synthesis of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
51
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 141 publications
(56 citation statements)
references
References 56 publications
(94 reference statements)
0
51
0
1
Order By: Relevance
“…All these things make it an ideal supporting material 31 , 35 . Nickel-based nanocomposite and MgFe 2 O 4 NPs have also been found to be worthy electrocatalysts for the reduction of p-nitrophenol 36 , 37 . Nanocomposites based on carbon-nanotubes adorned with various metals like platinum, silver, mono-metallic and bi-metallic-gold also exhibit exceptional electrocatalytic activity towards the reduction of p-NP 31 , 38 , 39 , but their small earth richness and high cost inhibit their useful applications.…”
Section: Introductionmentioning
confidence: 99%
“…All these things make it an ideal supporting material 31 , 35 . Nickel-based nanocomposite and MgFe 2 O 4 NPs have also been found to be worthy electrocatalysts for the reduction of p-nitrophenol 36 , 37 . Nanocomposites based on carbon-nanotubes adorned with various metals like platinum, silver, mono-metallic and bi-metallic-gold also exhibit exceptional electrocatalytic activity towards the reduction of p-NP 31 , 38 , 39 , but their small earth richness and high cost inhibit their useful applications.…”
Section: Introductionmentioning
confidence: 99%
“…Spinel ferrites of the form MFe 2 O 4 (M = Mg, Zn, Co, Ni) were synthesised at much lower reaction temperatures than comparable techniques by using a ChCl:maleic/malonic/oxalic acid, or ChCl:urea or ChCl:EG DES. 332,333 Jiang et al used a ChCl:triethanolamine DES to template a 3D porous nanostructure for NaTi 2 (PO 4 ) 3 , interesting as an anode for sodium-ion batteries once calcined with sucrose to cast it onto a carbon substrate. 334 In a control experiment, it was shown that aqueous mixtures of the HBD and salt respectively formed prismatic and globular nanoparticles.…”
Section: Deep Eutectic-solvothermal Synthesismentioning
confidence: 99%
“…Among these, carbon nanotubes have drawn attention since their inception in 1991, because of their unique properties including excellent electrical conductivity, large surface area, high electron density, exceptionally high mechanical and chemical stability, all of which makes them an ideal supporting material (Umar et al, 2016;Liu et al, 2018). Furthermore, the Ni based nanocomposite, MgFe 2 O 4 NPs proved to be a good electrocatalyst for 4nanoparticles (NPs) reduction (Baby et al, 2019;Mejri et al, 2019). Carbon nanotubes decorated with metals like Pt, Pd, Ag, monometallic-Au, and bimetallic-Au show excellent electrocatalytic activity toward nitrophenols (Liu et al, 2015;Umar et al, 2016;Sun et al, 2017;Dhanasekaran et al, 2019;Ding et al, 2019), but their low earth abundance and high cost inhibits their practical applicability.…”
Section: Introductionmentioning
confidence: 99%